The Crimes Of The Secret Army Organization In The City Of Oran during the Algerian Revolution through the Swiss Newspapers 1961- 1962 La Sentinelle A Model - Chaabouni, Amina (The Algerian Historical Journal, 2026)
During the last two years of the blessed revolution, the city of Oran witnessed an escalation in violence by the Secret Army organization, which concentrated its criminal operations in major cities. ", through explosions and terrorist operations that were exacerbated after the signing of the Evian Conventions and in which innocent citizens were killed, This has led to the Western media's interaction with the Swiss media in Algeria. in particular the written press concerned with the Algerian revolution and related matters, despite its diversity and divergence of orientations, I have decided to choose the newspaper (La Sentinelle) of Switzerland and its articles on the city of Oran during 1961-1962 as the subject of this study.